Religiosity and Participation in Islamic Organization among Indonesian Muslim in Sydney and Canberra - Dzuriyatun Toyibah (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Indonesian Islam has its own unique characteristics as it is inseparable from local traditions and has been connected to the role of Indonesian Islamic organizations such as Nahdlatul Ulama and Muhammadiyah. This study observes the religiosity among Indonesian Muslims in Australia, especially in Sydney and Canberra in 2018. By conducting an online survey with 108 respondents, the study found that beside mandatory religiosity, Indonesian Muslims still very often perform nahdliyin-related religious activities such as celebrating halal bi halal, performing selamatan, requesting dua from ustadz, performing tahlilan and commemorating maulid an-Nabi. However, they prefer to pray teraweh with 11 rakaats and only very few respondents chose often and very often for teraweh with 23 rakaats. While most respondents felt being part of Nahdlatul Ulama, very few of them were an active member and a board member in Nahdlatul Ulama or Muhammadiyah. This is very interesting given the current rise of Islamism among Indonesian Muslims in Indonesia and overseas, as well as efforts made by some Indonesian Islamic organizations to spread moderate Islam throughout Western countries.